Efek Ekstrak Etanol Daun Gendola Merah (Basella alba L.) terhadap Kadar Kreatinin, Ureum dan Deskripsi Histologis Tubulus Ginjal Tikus Putih Jantan (Rattus norvegicus) Diabetes yang Diinduksi Streptozotocin: Effect of Ethanolic Extract of Gendola Merah (Basella alba L.) Leaves on Creatinine, Urea, and Description of Histological Tubular Kidney of Diabetic Male Rats induced by Streptozotocin - Joni Tandi; Ayu Wulandari; Asrifa Asrifa (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
The objective of this study is to determine the effect and the effective dose of ethanolic extract of Red Gendola (Basella alba L.) leaves on creatinine, urea and description of histological tubular kidney of diabetic male rats induced by streptozotocin. 30 male rats devided into six groups : groups I, II, and III were the control groups and groups IV, V, and VI were the experimental groups. Groups II, III, IV, V, and VI are given induction of STZ 40 mg/kg BW in a single dose i.p on day 0. Normal control group I and negatif control group II were givenonly Sodium-CMC 0,5%; positive control group III was given glibenclamide 0,45 mg/kg BW; group IV, V, and VI were given each extract at a dose of 100, 200, and 400 mg/kg BW in p.o every day. The obtained data were analyzed using one way Anova test at the level of 95 % early followed by LSD Post Hoc Test, and the level of regeneration of histological tubularkidney was observed by HE staining using Olympus BX-51 microscope with a scale of 100 μm and scoring data result of kidney tubular damage levels were analyzed by Kruskal-Wallis test followed by Mann-Whitney test to see the differences between treatments.The results showed that ethanolic extract of red gendola with dose of 100 mg / kg BW give significant effect to decrease the creatinine content and 200 mg / kg BW give effect of decrease of ureum level of diabetic white male rats. Moreover, red gendola ethanolic extract has also an effect on cell regeneration in renal tubules with an effective dose of 400 mg /kg BW on diabetic male rats.